Biomechanical Characterization of Unilateral and Bilateral Posterior Lumbar Interbody Fusion Constructs. (13th August 2022) - Peng, Xiangping; Li, Shaoqing; Yang, Sidong; Swink, Isaac; Carbone, Jake; Cheng, Boyle; Wu, Zhanyong
Abstract : Study Design . Cadaveric biomechanical study. Objectives . To compare the biomechanical stability of two-level PLIF constructs with unilateral and bilateral pedicle screw fixations. Methods . Six cadaveric lumbar segments were evaluated to assess biomechanical stability in response to pure moment loads applied in flexion-extension (FE), lateral bending (LB), and axial rotation (AR). Each specimen was tested in six sequential configurations: (1) intact baseline; (2) facetectomy; (3) unilateral pedicle screws (UPS); (4) bilateral pedicle screws (BPS); (5) unilateral pedicle screws and cage (UPSC); and (6) bilateral pedicle screws and cage (BPSC). Results . Significant reductions in motion were observed when comparing all instrumented conditions to the intact and facetectomy stages of testing. No significant differences in motion between UPS, BPS, UPSC, or BPSC were observed in response to FE range of motion (ROM) or neutral zone (NZ). ROM was significantly higher in the UPS stage compared to BPS in response to LB and AT loading. ROM was significantly higher in UPSC compared to BPSC in response to LB loading only. Similarly, NZ was significantly higher in UPSC compared to BPSC in response to only LB loading. In response to AT loading, ROM was significantly higher during UPS than BPS or BPSC; however, no significant differences were noted between UPSC and BPSC with respect to AT ROM or NZ. Conclusion . BPS fixation is biomechanically superior to UPS fixation in multilevel PLIF constructs. This was most pronounced during both LB loading. Interbody support did contribute significantly to immediate stability.